2018
DOI: 10.1111/tesg.12332
|View full text |Cite
|
Sign up to set email alerts
|

Introduction To The Forum: From Third To Fifth‐Wave Gentrification

Abstract: ‘The Changing State of Gentrification’ (2001) by Jason Hackworth and the late Neil Smith is one of the most influential papers ever published in TESG. By introducing three waves, or periods, of practices and patterns of gentrification, it changed the way we think about gentrification. This Introduction to the Forum discusses the three waves introduced by Hackworth and Smith as well as fourth wave introduced by Lees et al. Finally, I will argue that during the global financial crisis we have entered fifth‐wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 61 publications
2
92
0
14
Order By: Relevance
“…Rather, neighbourhood change in Alfama is driven by the extra-local demand that tourism offers and the role of Airbnb in creating new real estate investment opportunities. We showed that 78% of Airbnb landlords are individual and corporate investors and, in this regard, we agree with Aalbers (2019) that Airbnb is an integral part of the current fifth-wave gentrification in which the arrival of global real estate capital into certain neighbourhoods increasingly drives the process.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 82%
“…Rather, neighbourhood change in Alfama is driven by the extra-local demand that tourism offers and the role of Airbnb in creating new real estate investment opportunities. We showed that 78% of Airbnb landlords are individual and corporate investors and, in this regard, we agree with Aalbers (2019) that Airbnb is an integral part of the current fifth-wave gentrification in which the arrival of global real estate capital into certain neighbourhoods increasingly drives the process.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 82%
“…The particular focus on small apartments in central locations likely contributes to further neighborhood gentrification, exacerbating divides between central and peripheral locations. This is in line with recent academic conceptualizations, linking contemporary (fourth or fifth-wave) gentrification to the financialization of housing and its increasing investment function (Aalbers, 2019;Lees et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…This is not to mention that Toronto's regulations are currently being appealed to what was formerly called the Ontario Municipal Board (OMB) 10a provincial planning institution with the power to override local land use decisionswhere they could potentially be struck down. 11 Insofar as Toronto's regulations are rejected at the provincial level, we might even expect big players like REITs to become entrepreneurial hosts in the short-term rental business, seeing it as a reliable mechanism for displacing tenants in the inner city for the higher revenues available in the tourism market (Aalbers, 2019;August & Walks, 2018). Furthermore, even in the event that commercial short-term rentals are effectively regulated out of existence, we must acknowledge that many low-income households have already been displaced.…”
Section: Resultsmentioning
confidence: 99%
“…Attention to this phenomenon has much to contribute to recent research describing forms of gentrification occurring outside the classic model of in-migration of owner occupiers (Aalbers, 2019;August & Walks, 2018;Jennifer & Vachon, 2008;Lees, 2017;Paccoud, 2016;Van Criekingen, 2010). Looking at dynamics in the traditional rental market, Paccoud shows how the recent rise of private landlords in the UK, facilitated by policies allowing and incentivizing "buy-to-let" mortgages, has resulted in displacement of lower-income renter populations for wealthier renters.…”
Section: Theorizing Short-term Rental Platforms As Tools For Gentrifimentioning
confidence: 99%